(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article explores the poetic features of the depiction and interpretation of religious-legendary and mythological images in modern Uzbek poetry. Mythological and religious-legendary images of dragon, “yuha”, jinn, devil, giant are metaphorized and stylized in modern Uzbek poetry. Their figurative meanings of evil, greed, horror, cruelty, huge, scattering fire, causing death are shown on the basis of examples from modern Uzbek poetry.